2015
DOI: 10.1111/jgs.13235
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E, Carbon Dioxide Vasoreactivity, and Cognition in Older Adults: Effect of Hypertension

Abstract: Objectives To investigate the associations between the apolipoprotein E (APOE) ε4 allele, carbon dioxide (CO2) vasoreactivity, and cognitive performance and to explore the effect of CO2 vasoreactivity and hypertension on the associations between APOE and cognition. Design Observational. Setting Community. Participants Older adults (N=625) enrolled in the Maintenance of Balance, Independent Living, Intellect and Zest in the Elderly of Boston Study Measurements Change in cerebral blood flow velocity in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 31 publications
1
23
1
Order By: Relevance
“…31 This is in line with a recent cross-sectional study, that found the impact of APOEε4 on cognition to be amplified in the presence of impaired vasoreactivity. 32 As imaging markers of both microvascular disease and cognitive function, such as white matter lesions and microbleeds, 9,33 are abundant in APOEε4 carriers, 34 specific APOE-related mechanisms may account for these observations. In fact, mechanisms described above in relation to inflammation, pericyte function, and blood-brain barrier integrity have been reported of particular relevance in APOEε4 carriers.…”
Section: Discussionmentioning
confidence: 99%
“…31 This is in line with a recent cross-sectional study, that found the impact of APOEε4 on cognition to be amplified in the presence of impaired vasoreactivity. 32 As imaging markers of both microvascular disease and cognitive function, such as white matter lesions and microbleeds, 9,33 are abundant in APOEε4 carriers, 34 specific APOE-related mechanisms may account for these observations. In fact, mechanisms described above in relation to inflammation, pericyte function, and blood-brain barrier integrity have been reported of particular relevance in APOEε4 carriers.…”
Section: Discussionmentioning
confidence: 99%
“…In knock-out mice models, the absence of APOE was associated with lower blood brain barrier integrity [31]. In humans, the APOE ε4 allele is associated with worse endothelial function [32], lower middle cerebral artery vasoreactivity to inhaled carbon dioxide [33], evidence of cerebrovascular disease on MRI [34] and greater decline in regional cerebral blood flow [35]. Most notably, the APOE ε4 allele is a susceptibility gene for Alzheimer’s disease [25, 26] and its presence increases the likelihood of cortical amyloid-β deposition in non-demented individuals [36].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, reduced CVRh is associated with hypertension (Hajjar et al 2010), cognitive decline (Pfefferkorn et al 2001; Silvestrini et al 2006; Vicenzini et al 2007; Cantin et al 2011; Zavoreo et al 2013), and is more sensitive to vascular burden as measured by the Framingham Stroke Risk Profile than resting CBF or brain volume (Glodzik et al 2011). In fact, results from a 2015 study suggest that APOE ε 4 carriers have lower CVRh than non-carriers and that the cognitive decline associated with the ε 4 allele is attributable to lower CVRh (Hajjar et al 2015). …”
Section: Future Directions and Emerging Biomarkersmentioning
confidence: 99%